Black suburbanization and the evolution of spatial inequality since 1970 - Alexander W. Bartik; Evan Mast (W.E. Upjohn Institute for Employment Research, 2021)
Since 1970, the share of Black individuals living in suburbs of larger cities has risen from 16 to 36 percent. We present three facts illustrating how this suburbanization has changed spatial inequality. First, suburbanization entirely accounts for Black households' relative improvements in several key neighborhood characteristics, while Black city dwellers saw declines. Second, suburbanization accounts for over half of the increase in within-Black income segregation. Selective Black migration and muted suburban "White flight" both contribute to these patterns. Third, total Black population in central cities has plummeted since 2000, driven by young people and declines in high-poverty, majority-Black neighborhoods.
Keywords: R23; J15; J11; 330; suburbanization; racial inequality